The Caliphate Paradigm as an Antithesis to Imperialism: A Theological and Geopolitical Analysis in the Discourse of Islamic and Western Civilizations - Supandi, Muhammad Diaz; Syaputra, Muhammad Bili; Afthon, Hilmi; Pradana, Aditya Rizki; Munawar, Ali Mahfuz (JIS: Journal Islamic Studies, 2025)
Global civilizational discourse remains entangled in epistemological asymmetries, wherein Western imperialism is exalted as a vehicle of progress while the Caliphate is vilified as a relic of despotism. This study interrogates such distortions, arguing that the Caliphate paradigm rooted in the Qur’anic principle of tawḥīd constitutes a theological and geopolitical antithesis to imperialism’s anthropocentric domination. Employing qualitative library research, this paper integrates critical discourse analysis, thematic Qur’anic exegesis (tafsīr maudūʿī), and comparative geopolitical insights through a decolonial epistemological lens (Santos). The findings reveal that the Caliphate positions sovereignty as a divine amānah, operationalized through maqāṣid al-sharīʿah, in stark contrast to the exploitative structures of imperialism evidenced by historical wealth extractions from colonized territories. Geopolitically, the Qur’anic ideal of ummah waḥidah (Q. 21:92) challenges colonial legacies of fragmentation, such as the Sykes-Picot Agreement, which has left 78% of Muslim-majority nations geopolitically vulnerable (FSI, 2023). Epistemologically, the paper advocates for an autonomous Islamic political framework by decentering Eurocentric constructs like the nation-state and rearticulating khilāfah beyond Orientalist tropes of tyranny (Said). In conclusion, the Caliphate is not a romanticized anachronism but a viable, justice-oriented paradigm—ontologically rooted in tawḥīd, geopolitically structured around unity, and epistemologically enabled through decolonized knowledge ecologies. It demands a reimagining of political theology that transcends imperial residues and asserts an authentically Islamic civilizational vision.